Partnership: a strategic paradigm for the production & management of affordable housing & sustainable urban development - Patrick Wakely (International Journal of Urban Sustainable Development, 2020)
Urban housing policies, in the opening decades of the 21st Century are in disarray. The objectives and targets set for the Sustainable Development Goals (SDGs) 2015–30 and the United Nations New Urban Agenda call for comprehensive urban housing policies, based on inclusion and participation. This paper argues for housing policies and implementation strategies that go beyond participation and are governed and managed by inclusive cost- and benefit-sharing partnerships of local government authorities and low-income group community members, NGOs and private sector stakeholders. Approaches to the formation and maintenance of democratic and equitable partnerships based on mutualism, interdependence, respect and trust are examined in the paper as a means to the efficient and effective production and management of affordable and sustainable housing and urban development; and as an end mechanism for the generation and strengthening of democratic, equitable urban communities, social change and poverty reduction and the alleviation of its impact.